Building Digital Trust in E-Commerce: An Analysis of Factors Influencing Customer Expectations Towards Shopee Purchases in Malaysia - Zi Jian Oh; Dung Gadi Paul; Sharma Brahmmanand; Ping Chuan Lai; Dor Wey Lam; Chia Yin Lee; Long Zheng Lee; Dubey Medha; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
Shopee, which was introduced in 2015, is the most popular e-commerce site in Southeast Asia. At the moment, it is among Malaysia's top e-commerce sites. Simple, Happy, and Together are the three defining characteristics of the community that Shopee aims to create by connecting customers and sellers. This study analyzes the factors influencing customer expectations toward Shopee purchases. Four contributing factors towards customer expectations were evaluated, specifically perceived convenience, perceived loyalty, perceived risk, and perceived trust. To analyze how customer experience influenced customer expectations on Shopee purchases, such as delivery speed, product quality, pricing, and customer service. A total of 150 customers from Shopee Malaysia participated in the survey questionnaire for data collection. The findings revealed that perceived trust and perceived convenience significantly and positively influenced customer expectations, while perceived risk indicated a significant negative impact. Meanwhile, perceived loyalty did notsignificantly influence customer expectations towards Shopee purchases. This survey gives Shopee important information and direction about how customers view Shopee, which increases customer happiness.